2017
DOI: 10.4149/neo_2017_414
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative mean platelet volume and platelet distribution associated with thyroid cancer

Abstract: Thyroid cancer is the most frequent cancer of the endocrine glands and the fifth most frequent cancer in women. Activated platelets play a crucial role in thrombosis, inflammation, and cancer. Mean platelet volume (MPV) and platelet distribution width (PDW) are early index of platelet activation. The purpose of this study is to investigate platelet indices levels in thyroid cancer. The study enrolled 280 patients with thyroid cancer and 280 control subjects. Patients' characteristics and hematologic tests data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 22 publications
3
27
0
3
Order By: Relevance
“…Moreover, increased PDW levels were positively correlated with MPV values and inversely correlated with platelet counts. Several of our findings concur with studies of various populations [5][6][7][8][9][10][11][12]. PDW is an indicator of heterogeneity in platelet size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, increased PDW levels were positively correlated with MPV values and inversely correlated with platelet counts. Several of our findings concur with studies of various populations [5][6][7][8][9][10][11][12]. PDW is an indicator of heterogeneity in platelet size.…”
Section: Discussionsupporting
confidence: 91%
“…Increased PDW values have been reported in patients with diabetes mellitus [5], cancer [6,7], and cardiocerebrovascular and respiratory disorders [8][9][10][11][12]. Moreover, higher PDW levels have recently been reported to be associated with increased morbidity and mortality among patients with critical illness [11,13], coronary artery disease [14][15][16][17], cancer [18][19][20][21], pulmonary embolism [10,22], and chronic obstructive pulmonary disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…The MPV is an important platelet indicator and as a marker of platelet size and activation. High MPV value is explained by a biologic explanation that larger platelets are more active in metabolic and enzymatic manner and tend to aggregate, resulting in thrombus or endothelial dysfunction than smaller platelets, as more and more research has been found that MPV is associated with prehypertension and hypertension (Varol et al ., ), type 2 diabetes (Chen et al ., ), familial hypercholesterolemia (Icli et al ., ), cancers (Kemal et al ., ; Kumagai et al ., ; Li et al ., ; Yu et al ., ), and many vascular diseases. Briefly, many studies have found that MPV associate with many vascular complications by means of endothelial damage and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils and other immune system cells secrete tumor growthpromoting factors, such as vascular endothelial growth factor, hepatocyte growth factor, interleukin 6, and interleukin 8, and the growth of tumor cells is stimulated. Therefore, increased NLR and interleukin levels are accompanied by peritumoral macrophage infiltration and this indicates a poor prognosis [18].…”
Section: Original Research Articlementioning
confidence: 99%